1997
DOI: 10.1172/jci119354
|View full text |Cite
|
Sign up to set email alerts
|

Impaired microvascular dilatation and capillary rarefaction in young adults with a predisposition to high blood pressure.

Abstract: Increased vascular resistance in essential hypertension occurs mainly in microvessels with luminal diameters Ͻ 100 m. It is not known whether abnormalities in these vessels are a cause or consequence of high blood pressure (BP). We studied 105 men (aged 23-33 yr) in whom predisposition to high blood pressure has been characterized by both their own BP and those of their parents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
186
3
7

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(208 citation statements)
references
References 37 publications
12
186
3
7
Order By: Relevance
“…Some authors consider this rarefaction a form of autoregulation, reflecting the long-term adaptation of microcirculation to the elevated blood pressure or the initial increase of blood flow. 11 Our study also agreed with the results of Noon et al, 12 who found that people with high blood pressure whose parents also had high blood pressure had fewer capillaries on the dorsum of their fingers, suggesting that defective angiogenesis may be an etiological component in the inheritance of high blood pressure. 12 Also, Draaijer et al 13 found that sodium-resistant borderline hypertensives had a possible structural reduction in nailfold skin capillary density when compared with both sodium-sensitive and control subjects.…”
Section: Discussionsupporting
confidence: 91%
“…Some authors consider this rarefaction a form of autoregulation, reflecting the long-term adaptation of microcirculation to the elevated blood pressure or the initial increase of blood flow. 11 Our study also agreed with the results of Noon et al, 12 who found that people with high blood pressure whose parents also had high blood pressure had fewer capillaries on the dorsum of their fingers, suggesting that defective angiogenesis may be an etiological component in the inheritance of high blood pressure. 12 Also, Draaijer et al 13 found that sodium-resistant borderline hypertensives had a possible structural reduction in nailfold skin capillary density when compared with both sodium-sensitive and control subjects.…”
Section: Discussionsupporting
confidence: 91%
“…We and others have hypothesized that microvascular abnormalities may not only be a consequence of hypertension, but may in fact precede -and contribute to -the elevation of blood pressure, hence creating a vicious circle (6,23). Indeed, structural and functional microvascular abnormalities have been reported in normotensive subjects at risk for hypertension (14,(24)(25)(26). Our understanding of the role of obesity-associated microvascular abnormalities in the development of hypertension has been enhanced by studies in the spontaneously hypertensive rat.…”
Section: Discussionmentioning
confidence: 99%
“…Microvascular dysfunction has already been described in OB, 22 first-degree relatives of diabetic 23 and hypertensive patients, 24 polycystic ovary syndrome 25 and type 2 diabetes mellitus 17 using different methods. Our data confirmed that OW/obese, sedentary, non-smoking and normoglycemic …”
Section: Discussionmentioning
confidence: 99%